Euskal Herria Nora Zoaz? Basque Country yesterday, today and tomorrow = Euskal Herria nora zoaz? Kraj Basków wczoraj, dziś i jutro - Mirgos, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the article is focused on the past and present political and cultural situation in the Basque Country, acting at the same time attempt to reflect on the future of the region. For this pur-pose, the author referrs to the problem of Basque-Spanish relations, which a difficult past still affects. Particular attention was also paid to the Basque language which is a key element of Basque identity, including linguistic repression and reviving the phenomenon of euskary. She also emphasizes the growing importance of immigrants in the Basque society.
Keywords: Basque Country; euskara; multiculturalism; identity; immigration; Kraj Basków; wielokulturowość; tożsamość; imigracja